2005
DOI: 10.1177/1077801205280191
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Latinas’ Conceptualizations of Intimate Partner Violence

Abstract: This study was a qualitative investigation of the conceptualization of intimate partner violence (IPV) among immigrant Latinas. The research approach used was naturalistic inquiry: conducting research maintaining minimal interference with the phenomenon of interest. Findings revealed that the immigrant Latinas in this study were aware of the poor quality of intimate relationships in their community, were knowledgeable about IPV, and understood that IPV is an extensive problem in the immigrant Latino community.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 17 publications
5
51
1
8
Order By: Relevance
“…Abused Latina and Asian immigrant women face significant social, cultural, structural, and political barriers to patient-provider communication and help-seeking behaviors related to IPV. [71][72][73] U.S.-born ethnic minority women face similar barriers in addition to medical mistrust, perceived discrimination, and historical racism and trauma for both African Americans and indigenous Americans. 31 To appropriately respond to the health needs of these women, it is essential that these multiple stressors be considered simultaneously.…”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…Abused Latina and Asian immigrant women face significant social, cultural, structural, and political barriers to patient-provider communication and help-seeking behaviors related to IPV. [71][72][73] U.S.-born ethnic minority women face similar barriers in addition to medical mistrust, perceived discrimination, and historical racism and trauma for both African Americans and indigenous Americans. 31 To appropriately respond to the health needs of these women, it is essential that these multiple stressors be considered simultaneously.…”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…Gender disparities resulting from acculturation, or increased adoption of American values and norms, can lead to higher levels of stress in the Hispanic immigrant family. This can lead to an increased rate of IPV (Adames & Campbell, 2005;Klevens, 2007;Mattson & Ruiz, 2005).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Given that Latina women regularly report machismo as a source or trigger of IPV (Coffin-Romig, 1997;WHO, 2005), similar to what female IPV victims in the general population report when interviewed in shelters for victims, research results in this area continue to mystify and suggest the need for further qualitative research. Adames and Campbell (2005) found that that in the immigrant Latino community they studied qualitatively, intimate relationships are "characterized by men's domination and women's subordination." Similarly, many of the participants in our study were strongly convinced that partner violent men are more machista than others.…”
Section: The Participants' Experience Of Ipvmentioning
confidence: 97%